Relationship between castration and morbidity and their effects on performance and carcass quality - Newsom, Cora Jane (Kansas State University, 2009)
When purchasing feeder calves, bulls are typically discounted relative to steers. Most would agree that a discount is warranted but determining the appropriate discount to apply is considerably more difficult. Being able to calculate this discount under varying conditions would help stock operators maintain a certain level of profitability or recognize opportunities to make more profit when excessive discounts are being applied. The goals of this study were to determine how castration timing affects performance (as measured by average daily gain), morbidity, and carcass quality and how morbidity affects performance and carcass quality. Ordinary Least Squares regression and logit models were estimated to quantify the effects of various management and environmental factors on performance, morbidity, and carcass quality. These model estimates of production variables along with price and cost assumptions were used to calculate breakeven purchase prices and price discounts for bulls relative to steers, accounting for the possibility of contracting bovine respiratory disease, if owned for a short background period or if ownership is retained through slaughter. Model results confirm that late-castrated steers do indeed exhibit diminished performance and increased morbidity probabilities relative to early-castrated steers. Increased morbidity also decreases average daily gain. However, this study found that castration timing and morbidity during the backgrounding period have minimal effects on carcass quality, with morbidity only impacting hot carcass weight and castration timing significantly affecting days to market and only tending to impact hot carcass weight. Ultimately, based on 2009 market conditions, bulls should be discounted at feeder calf sales compared to steers. The average calf arrived at 459 pounds, and at this weight bulls should be discounted $4.69/cwt relative to the same weight steers. The discount increases to $5.37/cwt for 400 pound calves and drops to $4.20/cwt for 500 pound calves. If ownership is retained through slaughter, required discounts will change to $6.77/cwt, $4.91/cwt, and $7.55/cwt, respectively.
Keywords: castration; performance; morbidity; carcass quality; backgrounding; beef cattle; Agriculture, General (0473); Economics, Agricultural (0503)